2016
DOI: 10.1016/j.nurpra.2015.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Male, Female, Other: Transgender and the Impact in Primary Care

Abstract: Transgender includes patients at various stages of their journey. It is important that providers care for transgender patients with a culturally sensitive approach, awareness, and competent skill. There are new terms to learn. There may be mental health issues or substance use issues. Hormone therapy can have an impact on a person's health. As a primary care provider, it is important to be alert to these potential issues, addressing the patient's individual needs. In this study we discuss the transgender patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 7 publications
0
24
0
1
Order By: Relevance
“…safe sex, hormone therapy and gender reassignment surgery. The responses to each item was four point Likert type scale from very comfortable (4), somewhat comfortable (3), and somewhat uncomfortable (2) to very uncomfortable (1). This study reported a Cronbach alpha of .754 for internal consistency.…”
Section: Instrumentmentioning
confidence: 88%
See 1 more Smart Citation
“…safe sex, hormone therapy and gender reassignment surgery. The responses to each item was four point Likert type scale from very comfortable (4), somewhat comfortable (3), and somewhat uncomfortable (2) to very uncomfortable (1). This study reported a Cronbach alpha of .754 for internal consistency.…”
Section: Instrumentmentioning
confidence: 88%
“…Transgender is a term used to refer to a diverse group of individuals whose gender identity or behavior differs from what they were assigned at birth [1]. Transgender is a broad term that encompasses different gender-variant identities and expressions including transsexuals [2].…”
Section: Introductionmentioning
confidence: 99%
“…2015 UNAIDS data, the number of HIV cases in Indonesia ranges from 600,000 to 790,000 or with an estimated 690,000 People Living With HIV-AIDS (PLWH ) According to the 2015 Integrated Biological, and Behavior Surveillance, HIV prevalence in the transgender community in Indonesia was 25.8% or with an estimated size of 37,998 transvestites (UNAIDS, 2015;Codex & Commission, 2015). The number of individual transgender is difficult to estimated (Markwick, 2016;Baral et al, 2013). The reason is due to a lack of accurate data collection for transgender women or transgender man (Markwick, 2016;Brent, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of individual transgender is difficult to estimated (Markwick, 2016;Baral et al, 2013). The reason is due to a lack of accurate data collection for transgender women or transgender man (Markwick, 2016;Brent, 2016). The prevalence of HIV infection in transgender women is higher compared to female sex workers and male sex workers (Evans, Pablos-méndez, Group, & Agency, 2016;Poteat et al, 2014;Baral et al, 2013) Transgender individuals come from a variety of backgrounds, races, religions, ethnic groups, and socioeconomic status, with fully productive lives (Markwick, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation